Heteroskedastyczność grupowa i korelacja przekrojowa w analizach wykorzystujących próby czasowo-przekrojowe - Dańska-Borsiak, Barbara; Laskowska, Iwona (Groupwise heteroscedasticity and cross-sectional correlation in analyses based on time-series - cross-section data, 2006)
Time-series - cross-section data (TSCS) are used more and more often in analyses of complex economic and social phenomena. Having combined the two dimensions - time and space results very often in groupwise heteroscedasticity and/or cross-sectional correlation. If those phenomena are taken into account while estimating models based on TSCS data, it is possible to increase the effectiveness of estimates and to model the processes which generate their appearance. The methods of TSCS models testing and estimation are presented using a model of labour demand by PKD sections.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 186-193